التعليل بالحكمة عند الأصوليين وأثره في اختلاف الفقهاء: دراسة تحليلية: Reasoning based on wisdom among fundamentalists and its impact on the Disparities among the jurists: An analytical study - Moustapha Mbacke (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث تهدف الدراسة إلى التعرف على التعليل بالحكمة عند الأصوليين وأثره في اختلاف الفقهاء، وتكمن مشكلة الدراسة في أنّ التعليل بالحكمة لم يحظ بالاهتمام الكافي عند الأصوليين وخاصة في أصول الفقه وفي تفسير النصوص وتعليلها، وكذا في القياس والتفريع الفقهي للنصوص الشرعية، مما أدّى إلى تباين في آراء الفقهاء، وتبرز أهمية الدراسة في تسليط الضوء على التعليل بالحكمة عند الأصوليين، واتبعت الدراسة المنهج التحليلي لتحليل التعليل بالحكمة عند الأصوليين وأثره في اختلاف الفقهاء. فقد توصلت الدّراسة إلى العديد من النّتائج من بينها أنّ الحكمة من المسائل العقلية التي يمكن الاستدلال بها؛ أمّا مسالك الحكمة فهي تعود للنص صراحة؛ إذ إنّ النّص تَتَّضِحُ من ورائه العلة. ومن النّتائج أيضًا إعمال مسالك العقل الراجحة مثل المناسبة والسبر والتقسيم، وذلك لحساسية قيام العقل باستنباط الأحكام الشرعية. ولقد أوصت الدراسة بضرورة الاطلاع على كتب علم أصول الفقه. ABSTRACT: The study aims to identify the reasoning by wisdom among the fundamentalists and its impact on the differences in jurists. The problem of the study lies in the fact that the reasoning by wisdom has not received sufficient attention among the fundamentalists, especially in the principles of jurisprudence and in the interpretation and reasoning of texts, as well as in analogy and jurisprudential interpretation of legal texts, which has led to a discrepancy in opinions of the jurists, The importance of the study is highlighted in shedding light on the reasoning by wisdom among the fundamentalists. The study adopted the analytical approach to analyze the reasoning by wisdom among the fundamentalists and its impact on the differences of jurists. The major finding of the study is that wisdom is one of the mental issues that can be inferred; As for the paths of wisdom, they refer explicitly to the text. Because the reason behind the text becomes clear. Another finding also, is that the implementation of the predominant methods of reason, such as appropriateness, sounding, and division, due to the sensitivity of the mind’s ability to deduce legal rulings. The study recommended the necessity of reviewing books on the principles of jurisprudence.